Use of levothyroxine for euthyroid, thyroid antibody positive women with infertility: analyses of aggregate data from a survey of European thyroid specialists (Treatment of Hypothyroidism in Europe by Specialists: An International Survey) - Negro, Roberto; Žarković, Miloš; Attanasio, Roberto; Hegedüs, Laszlo; Nagy, Endre V.; Papini, Enrico; Akarsu, Ersin; Alevizaki, Maria; Ayvaz, Göksun; Bednarczuk, Tomasz; Beleslin, Biljana Nedeljković; Berta, Eszter; et al. (Clinical endocrinology, 2024)
Objectives The use of levothyroxine (LT4) treatment aiming to improve fertility in euthyroid women with positive thyroid peroxidase antibodies (TPOAb) is not supported by the available evidence. The aim of the study was to document the use of LT4 by European thyroid specialists in such patients. Design The data presented derive from Treatment of Hypothyroidism in Europe by Specialists, an International Survey (THESIS), a questionnaire conducted between 2019 and 2021 to document the management of hypothyroidism by European thyroid specialists. Here, we report the aggregate results on the use of LT4 in infertile, euthyroid women with positive TPOAb. Results A total of 2316/5406 (42.8%) respondents stated that LT4 may be indicated in TPOAb positive euthyroid women with infertility. The proportion of those replying positively to this question varied widely across different countries (median 39.4, range 22.9%-83.7%). In multivariate analyses males (OR: 0.8; CI: 0.7-0.9) and respondents >60 years (OR: 0.7; 0.6-0.8) were the least inclined to consider LT4 for this indication. Conversely, respondents managing many thyroid patients (“weekly” [OR: 1.4; CI: 1.0-1.9], “daily” [OR: 1.8; CI: 1.3-2.4]) and practicing in Eastern Europe (OR: 1.5; CI: 1.3-1.9) were most likely to consider LT4. Conclusions A remarkably high number of respondents surveyed between 2019 and 2021, would consider LT4 treatment in TPOAb positive euthyroid women with infertility. This view varied widely across countries and correlated with sex, age and workload, potentially influencing patient management. These results raise concerns about potential risks of overtreatment.